Learning to learn: comparing learning and teaching style - Floriana Falcinelli (Form@re : Open Journal per la Formazione in Rete, 2016)
The essay concerns a survey that has been made with the students and teachers of two secondary and high schools in Città della Pieve (PG - Italy). The aim of this survey is the knowledge comprehension and comparison of the students’ learning styles 1and the teachers’ teaching styles. In the educational environment the relevance of individual differences is unquestionable; the knowledge of students’ learning styles allows the teacher to take advantage of individual abilities. Two different questionnaires have been submitted and the results have been examined to analyse the students’ learning styles and to study the teachers’ teaching styles. The obtained data concern the fundamental themes related to the learning and teaching process. Imparare ad imparare: stili di apprendimento e di insegnamento a confronto Il contributo descrive l’indagine, condotta in due classi delle scuole secondarie di primo e secondo grado di Città della Pieve (PG), volta a rilevare e comparare gli stili di apprendimento degli studenti e gli stili d’insegnamento dei loro docenti. L’importanza di considerare le differenze individuali è per l’ambito educativo indiscutibile, dal momento che solo conoscendo le modalità attraverso cui gli studenti apprendono, un insegnante può riuscire a valorizzare le attitudini di ognuno. I risultati emersi dalla somministrazione di due distinti questionari, sono stati esaminati con il duplice scopo di: approfondire la conoscenza degli stili di apprendimento e avviare una riflessione sugli stili di insegnamento dei docenti. I dati raccolti toccano aspetti fondamentali delle tematiche legate ai processi di apprendimento e di insegnamento.